Answer: t=4.6*R*L
Explanation: In order to explain this problem we have to take into account the expression for the current in a RL electric circuit, which is given by:
![i(t)=if*(1-^(-t/R*L))](https://img.qammunity.org/2020/formulas/physics/college/3fea2pvpfn10sdjy4tub965ciuzvkk6qy9.png)
where If is the final current for RL circuit If (emf/R)
Considering the final current is getting when I(t) = 0.99*If we have:
![0.99*if=if*(1-^(-t/R*L))](https://img.qammunity.org/2020/formulas/physics/college/htjnuykbf1slb2wdtuqmkofzdvnmiiqezh.png)
reoganising the terms we have:
e^(-t/R*L)=(1-0.99)
ln(e^(-t/R*L))=ln(0.01)
then t=4.6*R*L